Pengembangan Media Interaktif Augmented Reality (AR) Pada Topik Mengenal Organ Pernapasan Manusia di Kelas V Sekolah Dasar - Umam, Azmil; Tanjung Sari, Tita; Puniman, Ach.; Daniel Wahyudi, Eko (Prodi Pendidikan Guru Sekolah Dasar, 2024)
The rapid development of technology provides various changes in human life factors. The world of education can take advantage of technological developments to encourage quality learning, one of which is by utilizing technology as one of the media to maximize the learning process. this study aims to: (1) To find out how the Development of Interactive Media Based on Augmented Reality (AR) on the Topic of Knowing Human Respiratory Organs in Class V Elementary School, (2) To find out how the teacher's response and student response to Interactive Learning Media Based on Augmented Reality (AR) on the Topic of Knowing Human Respiratory Organs in Class V Elementary School. This research is a development research using the 4-D development model from Thiagarajan which consists of design, define, develop, dessiminate. the results of the percentage of product feasibility from the validator are 90% material validation while 92.5% media validation with the category